HOTS in Arabic Learning: A Study of The Implementation of HOTS on Students' Critical Thinking Ability - Syaiful Mustofa; Ayu Desrani; Apri Wardana Ritonga (Universitas Islam Negeri Palangka Raya, 2022)
Seeing the increasingly fierce scientific competition in the international world, the government has begun to implement HOTS-based learning (Higher Order Thinking Skills) in the 2013 curriculum. HOTS has been applied in learning, including learning Arabic. Using HOTS-based Arabic learning is expected to produce human resources who can think critically about global issues and competition. This study aims to find the effect of learning Arabic based on HOTS and critical thinking skills. This study uses a mixed method approach called sequential explanatory design, started with quantitative and then followed by qualitative. The population in this study is students of X graders of MAN 1 Kota Malang. The data collection technique used is random cluster sampling using X graders of Language Class 1 as the experimental class and Language Class 2 as the control class. Collecting data is done using tests that is analyzed by independent sample t-test. The study results indicate that HOTS-based Arabic learning significantly affects students' critical thinking skills. It is shown by the average value of the experimental class students, which is 68.13, while the average value of the control class is 54.69, with a significance (sig-2 tailed) of 0.00 <0.05. It means that HOTS-based learning positively impacts learning Arabic so that it can improve students' ability to think critically. Further research is recommended to measure its effectiveness.